2018
DOI: 10.1016/j.jcs.2018.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Improving the extractability of arabinoxylans and the molecular weight of wheat endosperm using extrusion processing

Abstract: Cereal derived arabinoxylans (AXs) are non-starch polysaccharides that have immunomodulatory activities. These activities are thought to be related to the low molecular weight fractions of AXs. Wheat and wheat by-products are rich in AXs, however, the water extractable fraction of AXs in wheat products is low. Water extraction of AXs can be improved by extrusion processing, which increases the extractability of the water soluble fraction. The aim of this study was to determine the extractability and molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
9
1
Order By: Relevance
“…Different from other parameters, with the increase in screw speed from 13 Hz to 15 Hz ( Figure 1 d), the content of WEAX increased slightly from 1.84 g/100 g to 1.99 g/100 g ( p < 0.05), while there was a decrease to 0.88 g/100 g when screw speed increased to 17 Hz. This is different from the result of Fadel et al, who reported a tendency for WEAX content in defatted rice bran to increase with extrusion screw speed from 80 rpm to 160 rpm [ 6 ]. A higher extrusion speed will exert high shear force to liberate ferulic acid side chains esterified to AX residues, which might induce higher exposure of AX to water, thus increasing WEAX content [ 51 ].…”
Section: Resultscontrasting
confidence: 95%
See 1 more Smart Citation
“…Different from other parameters, with the increase in screw speed from 13 Hz to 15 Hz ( Figure 1 d), the content of WEAX increased slightly from 1.84 g/100 g to 1.99 g/100 g ( p < 0.05), while there was a decrease to 0.88 g/100 g when screw speed increased to 17 Hz. This is different from the result of Fadel et al, who reported a tendency for WEAX content in defatted rice bran to increase with extrusion screw speed from 80 rpm to 160 rpm [ 6 ]. A higher extrusion speed will exert high shear force to liberate ferulic acid side chains esterified to AX residues, which might induce higher exposure of AX to water, thus increasing WEAX content [ 51 ].…”
Section: Resultscontrasting
confidence: 95%
“…Arabinoxylan (AX) is the main DF in WB, accounting for over 50% of total dietary fiber (TDF) [ 6 ]. However, most AXs are embedded in the cell wall matrix and intertwined with other macromolecules, which makes them difficult to extract with water [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Arabinoxylans (AXs) are major non-starch polysaccharides (NSPs) in cereals. AXs have attracted attention due to their immunomodulatory activities (1) , which may be related to the content of low molecular weight (Mw, < 32 kDa) AXs, (1) . Rice bran (RB) is a rich source of AXs (1) but water extraction of RB AXs is difficult giving a low yield.…”
Section: Faculty Of Engineering Istanbul Aydın Univesity Istanbul Turkeymentioning
confidence: 99%
“…It was hypothesized that extrusion cooking increases dietary fibre solubility, probably due to the reduction in particle sizes of extruded samples [87] and/or the breaking down of covalent and non-covalent bonds in larger molecules due to the high temperature applied [88]. It was reported that extrusion of rice bran increases the extractable levels of AXs but decreases the A/X ratio and molecular weight compared with non-extruded samples [80,89]. Such an effect is likely to be owing to the high shear-stress forces and high temperatures applied that can cause the release of ferulic acid, softening of lignin and AXs depolymerization.…”
Section: Dietary Fibres Extracted From Cereal Processing By-productsmentioning
confidence: 99%
“…Arabinoxylans Fermentation [102][103][104] Ultrasonic/microwave [105,106] Enzymatic treatment [107][108][109][110] Milling fractions [111][112][113] Alkaline treatment [114][115][116][117] Nixtamalization [118] Starch removal [119] Extrusion [80,86,89,120] Subcritical water treatment [119,121] β-glucans Ultrasound [122] Roller-milling/pearling [123] Milling [124][125][126] Fermentation [127,128] Enzymatic treatment [129,130] Extrusion [131][132][133][134] Subcritical water treatment [119,135,136]…”
Section: Compound Techniques Referencesmentioning
confidence: 99%